24-MHz scanner for optoacoustic imaging of skin and burn - Vionnet, Laetitia; Gateau, Jerome; Schwarz, Mathias; Buehler, Andreas; Ermolayev, Volodymir; Ntziachristos, Vasilis (IEEE Transactions on Medical Imaging, 2014)
Optoacoustic (photoacoustic) imaging uniquely visualizes optical contrast in high resolution and comes with very attractive characteristics for clinical imaging applications. In this paper, we showcase the performance of a scanner based on a 24 MHz center-frequency 128 element array, developed for applications in dermatology. We perform system characterization to examine the imaging performance achieved. We then showcase its imaging ability on healthy tissue and cancer. Finally, we image burns and human lesions in vivo and gain insights on the benefits and challenges of this approach as it is considered for diagnostic and treatment follow-up applications in dermatology and beyond. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Animal models; Burn; Dermatology; Imaging; Opto acoustic; Photoacoustic; Skin